Fine-mapping of PmHHM, a broad-spectrum allele from a wheat landrace conferring both seedling and adult resistance to powdery mildew - Fu, Bisheng; Lin, Zhixin; Yan, Lijuan; Zhang, Qiaofeng; Liu, Caiyun; Cai, Jin; Guo, Wei; Liu, Ying; Zhai, Wenling; Gong, Shuangjun; Xu, Feng; Wu, Jizhong (Frontiers in Plant Science, 2025)
IntroductionCommon wheat is a leading global food crop that impacts food security. Wheat powdery mildew (PM), caused by Blumeria graminis f. sp. tritici (Bgt), poses a significant threat to grain yield and flour quality. The identification and utilization of broad-spectrum resistance genes against PM are essential for effective disease control.MethodsThe resistance spectrum test during the seedling stage and the identification of resistance during the adult stage were conducted to evaluate the wheat landrace Honghuamai (HHM). Five segregating populations were investigated to assess the inheritance of PM resistance in HHM. To map its PM resitance gene, bulked segregant analysis, molecular mapping and comparative genomic analysis were also used in the present study.ResultsHHM shows remarkable adult resistance in the field and is nearly immune to all 25 Bgt isolates used in seedling tests, making it an excellent source of PM resistance. PM resistance in HHM was determined by a single dominant gene, temporarily named PmHHM. It was then fine-mapped to an interval with a genetic distance of 0.0031 cM and a physical distance of 187.4 kb on chromosome 4AL of the Chinese Spring reference sequence v.2.1. Four genes were identified in the target region, three of which encode nucleotide-binding leucine-rich repeat (NLR) proteins. Comparative genomic analysis revealed presence/absence variations (PAVs) of the PmHHM locus among common wheat varieties.DiscussionThese closely linked molecular markers will not only benefit the cloning of the gene underlying PmHHM but also facilitate the efficient utilization of the gene in breeding programs.